Social Media Effectiveness as a Promotional Medium to Increase Sales Volume - Titi Andriyani; M Syahirman Yusi; Yusnizal Firdaus (Politeknik Negeri Sriwijaya, 2022)
This study aims to determine the effectiveness of social media as a promotional medium in increasing sales volume using the AISAS Model at the Return Space and Coffee Cafe in Palembang. Research time was 6 month. The research method was descriptive quantitative and qualitative research with a questionnaire method. Results: The AISAS variables with the indicator of